2016
DOI: 10.1093/ee/nvv230
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bees Avoiding Ant Harassment at Flowers Using Scent Cues

Abstract: Pollinators require resources throughout the year to maintain healthy populations. Along the urban-natural interface, floral resource availability may be limited especially when the system experiences extreme drought and fire threats. In such areas, succulents, such as Aloe spp., are commonly planted to serve as functional drought-tolerant, fire-protective landscaping, which can also support pollinator populations. However, access to this resource may be restricted by competition from other floral foragers, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Shifts in insect prey traits in response to predators include behavioral changes [7][8][9][10][11], life history adjustments [12][13][14], and physiological changes [15][16][17][18][19] (See Table 1 & 2 for behavioral and physiological changes, respectively). The majority of studies to date link NCEs to changes in behavior, including changes in feeding [20][21][22], oviposition [23,24], colonization or dispersal [25][26][27], host-plant preference or habitat use [28][29][30] and increased predator avoidance [31,32]. As a whole, prey tend to respond to predators by modifying their behavior to become less apparent and reduce predator encounters (i.e.…”
Section: Insect Responses To Predation Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts in insect prey traits in response to predators include behavioral changes [7][8][9][10][11], life history adjustments [12][13][14], and physiological changes [15][16][17][18][19] (See Table 1 & 2 for behavioral and physiological changes, respectively). The majority of studies to date link NCEs to changes in behavior, including changes in feeding [20][21][22], oviposition [23,24], colonization or dispersal [25][26][27], host-plant preference or habitat use [28][29][30] and increased predator avoidance [31,32]. As a whole, prey tend to respond to predators by modifying their behavior to become less apparent and reduce predator encounters (i.e.…”
Section: Insect Responses To Predation Riskmentioning
confidence: 99%
“…It is well established that insect predators use chemical cues to locate prey [39] and more recently it has been shown that prey have the ability to eavesdrop on predator chemical cues [8,32,36,40]. Studies examining the role of chemical cues in NCEs have investigated isolated semiochemicals [9,28], chemicals associated with consuming conspecifics [33], footprints or previous foraging of predators [41], and crushed predators applied to plants as a slurry [40]. Using an experimental arena where predators had previously foraged and were subsequently removed, researchers can isolate specific contact chemical cues as a source of information for prey.…”
Section: Chemical Detection Of Predatorsmentioning
confidence: 99%
“…In their study, Cembrowski et al ( 2014 ) observed ants directly attacking bees visiting the artificial flowers and some bees having trouble flying after the interaction. Similarly, the invasive Argentine ants ( Linepithema humile ) are known to reduce pollinator foraging behavior within the temperate zone (Lach 2008 ; Sidhu and Wilson Rankin 2016 ). This aggressive invasive species holds the potential to reduce pollinator visitation duration by 50% and pollinator visitation is three times more likely on flowers without scent cues (Sidhu and Wilson Rankin 2016 ).…”
Section: Ants As Consumers In Grasslandsmentioning
confidence: 99%
“…Many studies have shown that prey respond to predators by changing either their behaviour or physiology to reduce the risk of predation. These include increased predator avoidance (Wratten, 1976;Hoefler et al, 2012;Lee et al, 2014), reduced feeding (Rypstra & Buddle, 2013;Kaplan et al, 2014;Thaler et al, 2014), reduced oviposition (Wasserberg et al, 2013;Sendoya et al, 2009) and changes in host plant preference (Wilson & Leather, 2012;Sidhu & Wilson Rankin, 2016).…”
Section: Non-consumptive Effects In Conservation Biological Controlmentioning
confidence: 99%